Severe acute respiratory syndrome coronavirus-2 in post-laryngectomy patients: case series of four patients. Issue 8 (23rd August 2020) - Coleman, H; Sutherland, J; Calder, N
Abstract: Objective: To report our experience of diagnosis, investigation and management in patients who had undergone laryngectomy secondary to previous squamous cell carcinoma, who were subsequently infected with severe acute respiratory syndrome coronavirus-2 during the coronavirus disease 2019 pandemic. Case reports: Four post-laryngectomy patients with laboratory-proven severe acute respiratory syndrome coronavirus-2 infection were admitted to our institution from 1 March to 1 May 2020. All patients displayed symptoms of coronavirus disease 2019 and underwent investigations, including swab and serum sampling, and chest X-ray where indicated. All were managed conservatively on dedicated coronavirus disease 2019 wards and were discharged without the requirement of higher level care. Conclusion: It is hypothesised that laryngectomy may offer a protective effect against severe or critical disease in severe acute respiratory syndrome coronavirus-2 infection. We hope sharing our experience will aid all practitioners in the management of this, often intimidating, cohort of patients.